Risk understanding and risk acknowledgement: a new approach to environmental risk assessment in marine aquaculture. (12th March 2022) - Andersen, Lasse Berg; Grefsrud, Ellen Sofie; Svåsand, Terje; Sandlund, Nina
Abstract: A better understanding of the potential cumulative impacts of large-scale fish farming, could help marine aquaculture to become more environmentally sustainable. Risk assessment plays an important role in this process by elucidating the main challenges and associated risk factors. An appropriate aquaculture risk assessment should contribute to mutual risk understanding and risk acknowledgement among stakeholders, and thus common perspectives on measures and governance. In this paper, we describe an approach to risk assessment in marine aquaculture that aims to promote fruitful discussions about risk and risk-influencing factors across stakeholders with different value perceptions. We elaborate on the concept of risk and risk terminology and conclude that new aquaculture risk assessment methodology should be guided by risk science. The suggested methodology is based on the latest thinking in risk science and has been tested in a thorough study of environmental risk related to Norwegian aquaculture. The study shows that the new methodical approach has an immanent pedagogical potential and contributes to strengthening risk understanding and risk acknowledgement among stakeholders. In conclusion, the suggested risk assessment methodology has proved a valuable tool for marine scientists in analyzing, evaluating, and communicating environmental risk.